Drugs in the News: What Do the Afghan News Media Say About Illicit Drugs? - Mahmood, Sultan (Université d'Ottawa / University of Ottawa, 2013)
Globally, research has shown that media coverage of illicit drug issues can play an important role in influencing public opinion and shaping drug policies. However, in Afghanistan, the world’s largest opium producer, very little is known about the media coverage of illicit drug issues. Afghan media, especially radio and television have developed dramatically during the past 11 years. Using the theories of agenda setting and framing, this study explored what drug-related topics were covered in the Afghan news media; how were these topics covered; how were the health and social consequences of drug abuse depicted in the media; and how much time was devoted to drug related topics in the media. Employing content analysis, the study examined primetime news coverage of the two leading media outlets: Azadi Radio and Tolo Television from 1st March 2011 until 31st July 2011. This thesis found the following types of imbalances in Afghan media reporting on illicit drug issues: 1) media reports on drug issues were heavily focused on supply reduction issues (81%) while paying considerably less attention to drug demand reduction issues (19%); 2) media predominantly framed illicit drugs as a law enforcement issue (83%) with only 15% of the paragraphs in the sample framing illicit drug as a public health problem; 3) media reporting on illicit drugs heavily relied on official sources (79%) lacking voices of the public health practitioners and drug addicts; 4) media coverage of illicit drug issues was heavily centered in Kabul (56%) with considerably less reporting from southern Afghanistan, which is the largest opium producing region. This study, which is presumably the first of its kind, provides media organizations, policy makers, and public health officials with a broad picture on the drug-related information available to the public on the leading Afghan news outlets. In addition, it serves as a basis for future research on media coverage of illicit drug issues in Afghanistan.
Keywords: drugs; media; Afghanistan; agenda-setting; framing